Interacción de mercados laborales municipales en el estado de Tabasco : una aproximación a través del uso de modelos gravitatorios - Juárez Aguirre, Eduardo (El Colegio de México A.C., 1993)
It is important to undestand economic and demographic intrastate interactions in order to formulate state policy. The interaction of municipal labor markets can only be understood through research models that allow us to incorporate the market's potential as well as the limitations brought about by geographical location.This study is based on the hypothesis that although the growth of labor markets depends upon the increase in demand for laborers, the short term increase of supply depends upon mobility -thè possibility to commute from one place to another. Whitin this framework, alternatives for growth available to labor markets at the state level are distributed in descending order according to the size the economically active population in the particular locality, the level of participation of the unemployed, and the distance between localities. Adopting the premise that demographic growth "follows" economic growth, we can assume that the possibility of growth in alternative labor markets -those not located in major towns- also represents the possibility of a concentrat of economic activities in sites other than the principal towns in the state.This study analyses the seventeen "county" or municipio seats in the State of Tabasco. The author uses gravitational models in order to delineate the interaction between local labor markets. Out of the seventeen, the top five are the principal points of expulsion, and the remaining twelve are the main points of attraction. The data for this study comes from the Eleventh (1990) General Population and Housing Census (INEGI, 1991).The principal results of the study are: a) the most important interactions between labor markets take place in the central region of the state, where Cunduacán and the axis of Tacotalpa-Teapa play an important role as alternatives for the growth of labor markets; b) there is another nucleus of interaction in the southern portion of the state, where Emiliano Zapata plays a relevant role as communicator with the central region; and c) the coastal region does not represent an alternative source of employment, at least not from the point of view of the principal "countries" of the state.